Hidden Voices: Students Views on amount of Loans received and Survival Mechanism in Tanzania Higher Learning Institutions - Sululu, Jacob; George, Victor; Kahimba, Joseph (Papanda Publishier, 2024)
The increasing use of student’s loans schemes to finance higher education is currently a global concern. It fuels access to higher education mostly to children from low-income families which ultimately strengthen equitable human capital growth. However, due to the increasing demand for higher education coupled with lower budget, many governments especially those in developing Countries fail to accomplish this task adequately. This study therefore, thought to assess students views on the amount of loan allocated and status of their survival in Tanzania Higher education Institutions. The aim is to see whether the received loan amount sufficiently cover their degree program cost, and if not, what are survival mechanisms are they make to supplement the discrepancy. The cross-sectional survey of 480 loans beneficiaries was adopted to collect data from four sampled universities. Data were analysed using descriptive and inferential statistics. The findings revealed that, due to the increasing trends of loans applicants’ and lower government budget, many students are allocated lesser amount of loan which eventually hinder their survival. As such others decide to engage on informal income generating activities which ultimately affect their academic progress. This study recommends on increased amount of loans allocation to students, as long as what they receive will be paid it back if adequate repayment strategies a put in place.